Influence of sheep manure, vermicompost and Azotobactor sp. on growth and yield of ajowan (Trachyspermum ammi Sprague) - B B Vashishtha, S S Meena, R S Mehta (Journal of Spices and Aromatic Crops, 2009)
A field experiment was conducted at Ajmer (Rajasthan) to study the influence of sheep manure,vermicompost and bio-fertilizer on growth and yield of ajowan (Trachyspermum ammi). Theexperiment consisted of 16 treatments comprising of three levels of sheep manure (5.0, 7.5,and 10.0 t ha-1), three levels of vermicompost (2, 3, and 4 t ha-1) and recommended fertilizerdose (90 kg N, 40 kg P2O5 and 30 kg K2O ha-1) with and without Azotobactor sp. and control.The results revealed that application of Azotobactor sp. alone and with sheep manure,vermicompost and recommended fertilizer dose resulted in higher growth parameters, yieldattributes and yield of ajowan over control. Increasing levels of sheep manure (5.0, 7.5 and10.0 t ha-1) and vermicompost (2, 3, and 4 t ha-1) exhibited higher yield over their respectivelower doses. The highest seed (16.35 q ha-1), stover (33.14 q ha-1) and biological yield (49.49 qha-1) of ajowan was obtained with application of sheep manure @ t 10 ha-1 with Azotobactorsp.